The response of rice (Oryza sativa L.) to elevated night temperature with application of Pyraclostobin - T Y Wahjanto; H T Sebayang; K P Wicaksono (Brawijaya University, 2016)
Rice productivity is having a problem related with climate change phenomenon, mainly the global warming. The rising of temperature in some country threat the rice production. The increasing of temperature is a major limiting factor that affects yield through the growth and development of rice plant. This study was aimed to examine the response of rice (Oryza sativa L.) to elevated night temperature with the application of Pyraclostobin. A glasshouse experiment that was conducted from March to August 2015 at Brawijaya University Research Station of Jatikerto – Malang, used nested plot design with three replications and two treatments. The first treatments were the night temperature level (normal temperature, increased 2oC, and increased 4oC). The second treatments were the concentration of Pyraclostrobin (0 ppm, 400 ppm and 800 ppm). Results of the study showed that the increase of temperature at night for about 2oC and 4oC, as well as application of Pyraclostrobin, affected growth and yield of rice. Application of Pyraclostrobin by concentrations of 400 ppm and 800 ppm effectively reduced yield loss by increasing night temperature of 2oC, which resulted in 20.20% and 24.93%, respectively, in comparison with the control; while the increase of night temperature by 4oC have resulted 26.86% and 33.33% in comparison with the control. Pyraclostrobin was effective in maintaining percentage of the filled spikelets by the increase of temperature at night for about 2oC and 4oC.